KADIN-MERKEZLİ BİR İSLÂMÎ TEOLOJİ İNŞASINA DOĞRU MU? - Adnan Bülent Baloğlu (İslami İlimler Dergisi)
It is a common saying among Western women theologians that patriarchal interpretation of the religious texts is the main cause for prejudices, oppressions and atrocities against women around the world. In this respect, in recent years, there has been a noticeable increase in the number of such works which were written with the aim of including women’s perspectives and experiences into the interpretation of religious texts. Such efforts and activities started in the West are also gaining popularity in the Muslim world. An overwhelming number of Muslim women theologians and researchers devoted themselves to the understanding and interpretation the religious texts, and produced a large number of works dedicated to the subject-matter. Their basic aim is that the Qur’anic verses and the Prophetic traditions were distorted in order to degrade women and put them under men’s yoke. Their proposal about what should be done about the distortion of the religious texts by patriarchal order is that these texts should be reconsidered and reinterpreted by the competent and qualified women theologians, researchers and writers. Only then can women reach their high ideals of freedom, equality, and justice, and only then can they recapture their dignity and rights which were usurped by men for ages. If all these aims and goals necessitate a new and fresh theology, doubtlessly it does so, then its name is “a women-centered Islamic theology”. When such theology established, women will be freed from the burden that men placed upon them, and make themselves visible with their womanhood, experiences, and perspectives not only in the field of religion, but also in society and culture.